Epstein–Barr virus-associated T- and NK-cell lymphoproliferative diseases: an update and diagnostic approach - Hue, Susan Swee-Shan; Oon, Ming Liang; Wang, Shi; Tan, Soo-Yong; Ng, Siok-Bian (Pathology, 2020)
Epstein–Barr virus (EBV)-positive T-cell and natural killer (NK)-cell lymphoproliferative diseases (EBV-TNKLPD) are a group of uncommon disorders characterised by EBV infection of T- and NK-cells. As a group, EBV-TNKLPD are more commonly encountered in Asians and Native Americans from Central and South America compared to Western populations. They encompass a spectrum of entities that range from non-neoplastic lesions such as EBV-associated haemophagocytic lymphohistiocytosis (EBV-HLH) to more chronic conditions with variable outcomes such as chronic active EBV infections (CAEBV) of T- and NK-cell type (cutaneous and systemic forms) and malignant diseases such as systemic EBV-positive T-cell lymphoma of childhood, aggressive NK-cell leukaemia, extranodal NK/T-cell lymphoma, nasal-type, and primary EBV-positive nodal T/NK-cell lymphoma. Due to their rarity, broad clinicopathological spectrum and significant morphological and immunophenotypic overlap, the diagnosis and precise classification of EBV-TNKLPD often pose a challenge to clinicians and pathologists. Correct classification of this group of rare diseases relies heavily on the age of onset, disease presentation, duration of symptoms and cell of origin (T- vs NK-cell lineage). In this review, we provide an update on the clinicopathological and molecular features of the various EBV-TNKLPD entities occurring in non-immunocompromised patients and present a practical algorithmic approach for the general pathologist who is confronted with these disorders in routine clinical practice.